2014
DOI: 10.1021/am500996c
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive Freestanding Graphene Films as Anode Current Collectors for Flexible Lithium-Ion Batteries

Abstract: The electrodes in lithium-ion batteries (LIBs) are typically films that are arranged on metal foil current collectors with a thickness of several tens of μm. Here, we report on the preparation of a thick free-standing graphene film synthesized by CVD as an alternative to Cu foil as an anode current collector. As a model system, MoS2 anodes with a flower-like morphology were anchored onto the surface of the thick graphene film. A hybrid and binder free anode without a conventional metal current collector exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Large-area graphene films obtained by a chemical vapor deposition (CVD) growth method are transferable onto any substrate, including flexible and stretchable materials. [1][2][3][4] These films have therefore opened a path for the development of large-area electrical and optical applications, including electrodes for Li-ion batteries, 5,6 supercapacitors, 7,8 and flexible transparent conducting films, [9][10][11] because of their good chemical stability, high flexibility, excellent carrier mobility, and lightweight structures. [12][13][14][15][16][17] However, various problems remain to be solved to enable the practical application of large-area graphene electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Large-area graphene films obtained by a chemical vapor deposition (CVD) growth method are transferable onto any substrate, including flexible and stretchable materials. [1][2][3][4] These films have therefore opened a path for the development of large-area electrical and optical applications, including electrodes for Li-ion batteries, 5,6 supercapacitors, 7,8 and flexible transparent conducting films, [9][10][11] because of their good chemical stability, high flexibility, excellent carrier mobility, and lightweight structures. [12][13][14][15][16][17] However, various problems remain to be solved to enable the practical application of large-area graphene electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Rana et al [ 146 ] obtained fl ower-like MoS 2 particles anchored onto the surface of graphene fi lms via CVD. The hybrid delivered a capacity of ≈580 mAh g −1 at 50 mA g −1 .…”
Section: Mos 2 -Graphene Hybridmentioning
confidence: 99%
“…Guo et al observed graphene‐like MoS 2 flakes when using a thermal decomposition approach. Rana et al obtained flower‐like MoS 2 particles anchored onto the surface of graphene films via CVD. The hybrid delivered a capacity of ≈580 mAh g −1 at 50 mA g −1 .…”
Section: Anode Materialsmentioning
confidence: 99%
“…Graphene membranes are reported as freestanding films [34][35][36][37][38][39] or supported ones [40,41]. However, most water treatment processes are subjected to high pressures, so that membranes must be robust enough to operate for long periods, therefore supported membranes are preferred.…”
Section: Introductionmentioning
confidence: 99%